The protective effect of vitamin C on phenylhydrazine-induced hemolytic anemia on sperm quality and in-vitro embryo development in mice - Mojtaba Karimipour; Zahra Dibayi; Abass Ahmadi; Masoumeh Zirak Javanmard; Elnaz Hosseinalipour (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Phenylhydrazine (PHZ) induced anemia and was shown to have harmful effects on the male reproductive system. Objective: To investigate the protective effect of vitamin C (Vit C) on sperm parameters quality, in vitro fertilization potential and embryonic development in a mouse model of hemolytic anemia induced by PHZ. Materials and Methods: Thirty-two NMRI adult male mice (n = 8/each) were randomly classified into four groups. Group I (control) received normal saline, Group II (PHZ) received 8 mg/100 gr body weight PHZ as initial dose, continued by 6 mg/100 gr intraperitoneally every 48 hr, Group III (Vit C) received Vit C (10 mg/kg, daily, intraperitoneally), and group IV (PHZ + Vit C) received PHZ and Vit C. After 35 days, sperm quality parameters, the percentage of sperm with DNA damage and in vitro fertilization outcomes up to blastocyst stage were evaluated. Results: A significant (p < 0.001) reduction in all of the sperm parameters (count, motility, viability and normal morphology) were observed in group II (PHZ) compared with group I (control). In group IV (PHZ ± Vit C), these parameters and sperm DNA damage (p < 0.001) improved significantly when compared with PHZ-treated mice. Furthermore, PHZ caused a significant (p < 0.001) decrease in the fertilization rate and the percentage of pre-implantation embryos' (two cell embryo and blastocyst) formation in comparison to group I (control), and Vit C supplementation in mice of group IV improved significantly the fertilization rate (p = 0.002), but it could not improve the percentage of two cell embryos and blastocyst production. Conclusion: The data from this study indicated that Vit C decreased the adverse effects of PHZ on the quality of sperm parameters and in vitro fertilization rate, but it is insufficient to restore the in-vitro embryonic development and fertility potential.